ИННОВАЦИОН ЕТАКЧИЛИК ФАОЛИЯТИНИНГ ИЖТИМОИЙ - ПСИХОЛОГИК ТАДҚИҚОТЛАРДА ЎРГАНИЛГАНЛИГИ - Нурабуллаев, Т.А. (SCIENCE and SOCIETY, 2022)
The article deals with the research of innovative leadership activity in the field of psychology, socio-psychological research, as well as the opinions of researchers on innovative leadership activity.